Modulation of CYP450 Activities in Patients With Type 2 Diabetes. Issue 6 (9th July 2019) - Gravel, Sophie; Chiasson, Jean‐Louis; Turgeon, Jacques; Grangeon, Alexia; Michaud, Veronique
Abstract : We conducted a comprehensive in vivo study evaluating the influence of type 2 diabetes (T2D) on major cytochrome P450 (CYP450) activities. These activities were assessed in 38 T2D and 35 non‐T2D subjects after a single oral administration of a cocktail of probe drugs: 100 mg caffeine (CYP1A2), 100 mg bupropion (CYP2B6), 250 mg tolbutamide (CYP2C9), 20 mg omeprazole (CYP2C19), 30 mg dextromethorphan (CYP2D6), 2 mg midazolam (CYP3As), and 250 mg chlorzoxazone (alone; CYP2E1). Mean metabolic activity for CYP2C19, CYP2B6, and CYP3A was decreased in subjects with T2D by about 46%, 45%, and 38% ( P < 0.01), respectively. CYP1A2 and CYP2C9 activities seemed slightly increased in subjects with diabetes, and no difference was observed for CYP2D6 or CYP2E1 activities. Several covariables, such as inflammatory markers (interleukin (IL)‐1ß, IL‐6, gamma interferon, and tumor necrosis factor alpha), genotypes, and diabetes‐related and demographic‐related factors were considered in our analyses. Our results indicate that low chronic inflammatory status associated with T2D modulates CYP450 activities in an isoform‐specific manner.